"Why you Throwing Subs?": An Exploration of Community College Students' Immediate Responses to Microaggressions. Issue 9 (September 2018) - Casanova, Saskias; Mcguire, Keon M.; Martin, Margary
Background/Context: Current research within four-year university settings reveals the daily encounters students of color and faculty have with microaggressions—brief, intentional or unintentional comments and behaviors communicating covert biases toward individuals based on their social group membership. The majority of all undergraduate students of color currently attend community colleges, but the occurrence of microaggressions in the community college classroom has been overlooked. We situate our study of microaggressions within the racial microaggressions model framework, which addresses how microaggressive events are mediated by institutional racism through systematic policies, practices, and processes that (re)produce inequitable stratification in higher education. Further, we analyze the immediate effects of and students' responses to classroom microaggressions. Purpose/Objective/Research Question/Focus of the study: The present study explores students' immediate responses to 51 microaggressions observed in three community colleges. We examine microaggressions in community colleges with the objective to provide a lens into the immediate effects and responses students display to observed classroom microaggressions. In exploring both the effects on students and their responses to microaggressions experienced in 17 classrooms, we gain insight on how these events contribute to or undermine students' in-the-moment learning experiences, as well as target their academic identities. To this end, we examine the following research questions: 1) In what ways were students' academic identities targeted by these microaggressions? 2) What were the immediate effects of and students' responses to the microaggressions experienced in their classrooms? Research Design: To examine our research questions, we utilize a mixed-method research design, whereby mixed-method "connecting" was used to systematically quantify the microaggressions that occurred, which were qualitatively recorded in ethnographic fieldnotes from structured observations. We conducted content analyses of the observed microaggression ethnographic fieldnotes using the racial microaggressions model. Findings/Results: Microaggressions stigmatized multiple identities the students occupied (e.g., college student identity). Using the racial microaggressions model analytical framework, we found that the most common immediate effects of microaggressions were: disengagement, silence, and discomfort. Immediate responses included laughter and responding with a joke or distraction. While less common, students sometimes resisted through actions of peer support and questioning of the perpetrator. Conclusion/Recommendations: By expanding the racial microaggressions theoretical framework to develop an analytical frame that allows for the examination of responses to microaggressions, we can engage in a deeper understanding of the nature of the microaggressive classroom, and the ways that microaggressions target students' academic identities. As found in our study, some students are engaging in immediate resistant acts to counter the microaggressions they experience, which warrants deeper investigation. Facing the reality that students with marginalized identities are likely to experience microaggressions, institutions should assist students in developing strategic responses that will help them adapt, cope, and resist.